2022
DOI: 10.34203/jimfe.v8i1.4902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kriteria Spin off: Proyeksi Nilai Kecukupan Dana Tabarru Industri Asuransi Syariah Pendekatan ARIMA

Abstract: Penelitian ini bertujuan untuk menganalisis kemampuan Unit Usaha Syariah (UUS) yang belum melaksanakan spin off untuk mencapai kecukupan dana tabarru sebesar 50% dari dana induk perusahaan pada pada akhir 2024, sesuai dengan aturan Undang-undang nomor 40 tahun 2014 tentang perasuransian. Subjek penelitian ini adalah sejumlah 44 unit usaha asuransi syariah yang belum melaksanakan spin off dengan induknya. Pengukuran ini dilakukan dengan memproyeksi perbandingan nilai dana tabarru unit usaha syariah yang belum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Regarding the criteria for this spin-off, which regulate the achievement of Tabarru funds and an investment of 50% of the parent company’s insurance premium funds, this has been proven by previous research that has projected the achievement of Tabarru funds until the end of 2024. The results of this study proved that there is no Islamic insurance unit that can achieve value of 50% by the end of 2024 (Yustiani et al , 2022; Nurhayat, 2021). The Tabarru fund in this case represents the value of the premium received by the sharia insurance unit from the public, and then some of the premium are invested and reinsured into a larger insurance entity as a risk reduction strategy.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Regarding the criteria for this spin-off, which regulate the achievement of Tabarru funds and an investment of 50% of the parent company’s insurance premium funds, this has been proven by previous research that has projected the achievement of Tabarru funds until the end of 2024. The results of this study proved that there is no Islamic insurance unit that can achieve value of 50% by the end of 2024 (Yustiani et al , 2022; Nurhayat, 2021). The Tabarru fund in this case represents the value of the premium received by the sharia insurance unit from the public, and then some of the premium are invested and reinsured into a larger insurance entity as a risk reduction strategy.…”
mentioning
confidence: 72%
“…Yunus (2019) and Nurhayat (2021) investigated the spin-off criteria using the ARIMA method, but the object studied was only limited in which Yunus did the research only for life insurance and Nurhayat only took the object of a sharia public company. The results of the two studies showed that a 50% of the adequacy of Tabarru funds and investment will not be achieved until the end of 2024 (Yunus, 2019; Nurhayat, 2021; Yustiani et al , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation